The sustainability sweet spot at Jiu Zhen Nan Taiwan pastry - TAN, Hwee Hoon (Institutional Knowledge at Singapore Management University, 2023)
Set in 2022, the case follows the sustainability journey of Jiu Zhen Nan, a 133-year-old Taiwanese pastry brand headquartered in Kaohsiung, the southern city of Taiwan. Jiu Zhen Nan specialises in gourmet traditional Chinese Han pastry, often consumed during major festivals, weddings, and religious celebrations. The century-old brand has an established stronghold at domestic airports, high-speed rail stations, and upscale department stores. Eric Lee, Chairman and the fourth-generation owner, had been at the helm of the family firm since 1996. Given the increased focus on sustainability issues in recent years, he had aligned sustainability priorities with the baked goods business, its core values, and its long-term purpose. Since the mid-2010s, he had led the firm to achieve considerable progress on several aspects of sustainability – food ethics, environmental sustainability, social participation, the promotion of Han pastry culture, and talent cultivation. Those efforts were duly recognised, winning the firm an Excellence in Corporate Social Responsibility award from the CommonWealth Magazine twice, in 2019 and 2021. Lee conceded that realising sustainability goals needed time, given that it would not be a short-term pursuit but rather an ongoing commitment. As he mulled over the options for navigating the prevailing challenges amid the COVID-19 pandemic, he recognised that, at the same time, there was mounting pressure to take even more action toward reducing the business impact on climate change. What more could a food manufacturing business like Jiu Zhen Nan do for the good of the planet, the good of society, and its future success? Students will learn to identify CSR initiatives and assess whether CSR gives family firms a competitive advantage. They will attempt to explain the strategic decisions of family firms using socioemotional wealth theory and discuss how sustainability values influence succession. They will also examine how firms involve stakeholders in their CSR. The case is suitable for teaching undergraduate, postgraduate, and executive classes on family business, sustainability, and CSR.